0
$\begingroup$

Given the intermediate points $\alpha = (\frac{1}{2^n}, \frac{2}{2^n},...,1)$ and $y=\frac{1}{2^n}$. Prove that, the subtotal of $e$ on $(Z, \alpha)$ equals:

$$e^{y}\frac{e - 1}{\frac{e^y - 1}{y}} = e^yy\frac{e - 1}{e^y - 1}$$

This is currently my approach. The subtotal of $e$ on $(Z, \alpha)$ can be calculated directly like following:

$$ \sum_{i = 1}^{n}(\frac{i}{2^n} - \frac{i - 1}{2^n})e^{\frac{i}{2^n}} = y\sum_{i = 1}^{n}e^{\frac{i}{2^n}} = e^yy \sum_{i = 1}^{n}e^{i} = e^yy (\frac{1 - e^{n + 1}}{1 - e} - 1) = e^yy (\frac{e - e^{n + 1}}{1 - e}) $$

Hence the following equality must be true:

$$\frac{(e - 1)}{e^y - 1} = \frac{e-e^{n + 1}}{1 - e}$$

I can not go further by this point and would appreciate hints.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.